Heat-resistant resin composition and injection molded article thereof

By using a combination of a resin with a specific ratio of energy storage elastic modulus and a loss of elastic modulus when the hot plate is fused, the problem of plastic stretching during hot plate fusion is solved, and injection molded products with high temperature oxidation resistance and excellent appearance quality are achieved.

JP7663589B2Active Publication Date: 2025-04-16DENKA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022547533
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-09
Filing Date
2021-09-02
Publication Date
2025-04-16
Estimated Expiration
2041-09-02

AI Technical Summary

Technical Problem

When the hot plates are fused, the plastic tends to stretch into threads when pulled apart, causing damage to the finished surface.

Method used

Using a high-temperature antioxidant resin combination containing maleimide copolymer (A) and ABS resin, ASA resin, AES resin or SAN resin (B), the ratio of the energy storage elastic modulus (G') to the loss elastic modulus (G'') of the resin combination is 0.30 to 1.00 at 240°C.

Benefits of technology

This resin combination does not cause stretching when the hot plate is fused, and the injection molded product has excellent thermal resistance and appearance quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663589000001
    Figure 0007663589000001
  • Figure 0007663589000002
    Figure 0007663589000002
Patent Text Reader

Abstract

The present invention addresses the problem of providing a heat resistance resin composition that does not cause stringing when used in fusion-bonding using heated plates. The present invention provides a heat resistance resin composition which contains a maleimide copolymer (A) and at least one resin (B) selected from ABS resins, ASA resins, AES resins, and SAN resins, and in which the ratio G' / G'' of a storage modulus (G') and a loss modulus (G'') at an angular velocity of 0.63 rad / s at 240°C as measured in accordance with JIS K 7244-10, is 0.30-1.00.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat-resistant resin composition which reduces stringiness during hot plate fusion and an injection-molded article thereof. [Background technology]

[0002] Acrylonitrile-butadiene-styrene copolymer resin (ABS resin) is widely used in automobiles, home appliances, office equipment, housing construction materials, daily necessities, etc., taking advantage of its excellent mechanical strength, appearance, chemical resistance, moldability, etc. In applications requiring heat resistance, such as automobile interior materials, ABS resins containing maleimide copolymers as heat resistance imparting materials are also used (e.g., Patent Document 1, Patent Document 2). In addition, in bonding resins such as ABS resins, hot plate fusion, in which the resin is pressed against a metal plate heated to a high temperature and the molten resins are bonded together, is inexpensive and commonly used. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 57-98536 [Patent Document 2] Japanese Patent Application Publication No. 57-125242 Summary of the Invention [Problem to be solved by the invention]

[0004] However, when the resin melted by the hot plate is pulled away from the hot plate, the resin can become stretched into threads, causing stringiness, which can mar the appearance of the molded product.

[0005] An object of the present invention is to provide a heat-resistant resin composition that does not cause stringiness during hot plate fusion, and an injection-molded article thereof. [Means for solving the problem]

[0006] As a result of intensive research, the present inventors have found that a heat-resistant resin composition which does not cause stringiness during hot plate fusion and an injection-molded article thereof can be obtained by producing a heat-resistant resin composition which contains a maleimide-based copolymer (A) and at least one resin (B) selected from ABS resin, ASA resin, AES resin, and SAN resin, and which has a ratio G' / G'' of storage modulus (G') to loss modulus (G'') of 0.30 or more and 1.00 or less at 240°C and an angular velocity of 0.63 rad / s as measured according to JIS K 7244-10, and has thus completed the present invention.

[0007] That is, the present invention provides the following. (1) A heat-resistant resin composition comprising a maleimide-based copolymer (A) and at least one resin (B) selected from ABS resin, ASA resin, AES resin, and SAN resin, wherein the ratio G' / G'' of storage modulus (G') to loss modulus (G'') at 240°C and an angular velocity of 0.63 rad / s, as measured in accordance with JIS K 7244-10, is 0.30 or more and 1.00 or less. (2) The heat-resistant resin composition according to (1), which contains 5 to 40% by mass of the maleimide copolymer (A) and 60 to 95% by mass of the resin (B). (3) The heat-resistant resin composition according to (1) or (2), wherein the maleimide copolymer (A) is composed of 40 to 60% by mass of aromatic vinyl monomer units and 60 to 40% by mass of maleimide monomer units. (4) The heat-resistant resin composition according to any one of (1) to (3), which has a melt mass flow rate of 5 to 30 g / 10 min under conditions of 220° C. and 10 kg, as measured by the method described in JIS K 7210. (5) The heat-resistant resin composition according to any one of (1) to (4), which has a Vicat softening temperature of 105° C. to 130° C. as measured by the method described in JIS K-7206. (6) An injection-molded article using the heat-resistant resin composition according to any one of (1) to (5). (7) The injection molded article according to (6) above, which is used as an interior or exterior member of an automobile. Effect of the Invention

[0008] The heat-resistant resin composition of the present invention is less prone to stringiness during hot plate fusion and has excellent appearance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] <Terminology explanation> In the present specification, for example, the description "A to B" means A or more and B or less.

[0010] Hereinafter, an embodiment of the present invention will be described in detail.

[0011] The heat-resistant resin composition of the present invention is obtained by melt-kneading and devolatilizing extrusion in an extruder of a maleimide copolymer (A) and at least one resin (B) selected from SAN resin (styrene-acrylonitrile copolymer resin), ABS resin (acrylonitrile-butadiene-styrene copolymer resin), ASA resin (acrylonitrile-styrene-acrylic rubber copolymer resin), and AES resin (acrylonitrile-ethylene propylene rubber-styrene copolymer resin).

[0012] The maleimide copolymer (A) is a copolymer composed of aromatic vinyl monomer units and maleimide monomer units, and may further contain unsaturated dicarboxylic anhydride monomer units and vinyl cyanide monomer units as constituent units in the present invention.

[0013] The aromatic vinyl monomer unit is styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, ethylstyrene, p-tert-butylstyrene, α-methylstyrene, α-methyl-p-methylstyrene, etc. Among these, styrene is preferred. The aromatic vinyl monomer unit may be used alone or in combination of two or more kinds.

[0014] The maleimide monomer unit is, for example, N-alkylmaleimide such as N-methylmaleimide, N-butylmaleimide, and N-cyclohexylmaleimide, and N-phenylmaleimide, N-chlorophenylmaleimide, N-methylphenylmaleimide, N-methoxyphenylmaleimide, and N-tribromophenylmaleimide. Among these, N-phenylmaleimide is preferred. The maleimide monomer unit may be used alone or in combination of two or more kinds. For the maleimide monomer unit, for example, a raw material consisting of a maleimide monomer can be used. Alternatively, it can be obtained by imidizing a raw material consisting of an unsaturated dicarboxylic acid monomer unit with ammonia or a primary amine.

[0015] The unsaturated dicarboxylic anhydride monomer unit is maleic anhydride, itaconic anhydride, citraconic anhydride, aconitic anhydride, etc. Among these, maleic anhydride is preferable. The unsaturated dicarboxylic anhydride monomer unit may be used alone or in combination of two or more kinds.

[0016] The vinyl cyanide monomer unit is acrylonitrile, methacrylonitrile, ethacrylonitrile, fumaronitrile, etc. Among these, acrylonitrile is preferable. The acrylonitrile-based monomer unit may be used alone or in combination of two or more kinds.

[0017] The aromatic vinyl monomer unit of the maleimide-based copolymer (A) is preferably 40 to 60% by mass, and the maleimide-based monomer unit is preferably 60 to 40% by mass. More preferably, the aromatic vinyl monomer unit is 45 to 55% by mass, and the maleimide-based monomer unit is 55 to 45% by mass. When the constituent units are within the above ranges, the maleimide-based copolymer (A) has excellent fluidity, heat resistance, and thermal stability. Furthermore, when the aromatic vinyl monomer unit and the maleimide-based monomer unit are within the above ranges, the compatibility with at least one resin (B) selected from ABS resin, ASA resin, AES resin, and SAN resin described later is improved, and the impact strength of the heat-resistant resin composition is excellent. The contents of the aromatic vinyl monomer unit and the maleimide-based monomer unit are values ​​calculated from the results of 13C-NMR measurement.

[0018] From the viewpoint of efficiently improving the heat resistance of the heat-resistant resin composition, the midpoint glass transition temperature (Tmg) of the maleimide copolymer (A) is preferably 175° C. to 200° C., more preferably 185° C. to 200° C., and further preferably 195° C. to 200° C. The midpoint glass transition temperature (Tmg) is a value measured by DSC in accordance with JIS K-7121, and is a value measured under the measurement conditions described below. Device name: Seiko Instruments Inc. Robot DSC6200 Heating rate: 10℃ / min

[0019] In order to increase the midpoint glass transition temperature (Tmg) of the maleimide copolymer (A), the content of the maleimide monomer unit may be increased or a monomer having a high midpoint glass transition temperature (Tmg) may be copolymerized.

[0020] The weight average molecular weight (Mw) of the maleimide copolymer (A) is preferably 80,000 to 160,000, more preferably 80,000 to 120,000. If the weight average molecular weight (Mw) of the maleimide copolymer (A) is within the above range, the impact strength of the heat-resistant resin composition is excellent. In order to control the weight average molecular weight (Mw) of the maleimide copolymer (A), there are methods such as adjusting the solvent concentration and the amount of the chain transfer agent added in addition to adjusting the polymerization temperature, polymerization time, and amount of the polymerization initiator added. The weight average molecular weight of the maleimide copolymer (A) is a value measured in terms of polystyrene by gel permeation chromatography (GPC) and was measured under the following conditions. Device name: SYSTEM-21 Shodex (Showa Denko Co., Ltd.) Column: 3 PL gel MIXED-B in series Temperature: 40℃ Detection: Differential refractive index Solvent: Tetrahydrofuran Concentration: 2% by mass Calibration curve: Prepared using standard polystyrene (PS) (PL Corporation).

[0021] A known method can be used to produce the maleimide copolymer (A). For example, there is a method of copolymerizing a monomer mixture consisting of an aromatic vinyl monomer, a maleimide monomer, an unsaturated dicarboxylic anhydride monomer, and other copolymerizable monomers. There is also a method of copolymerizing a monomer mixture consisting of an aromatic vinyl monomer, an unsaturated dicarboxylic anhydride monomer, and other copolymerizable monomers, and then reacting ammonia or a primary amine to imidize a part of the unsaturated dicarboxylic anhydride monomer units and convert them into maleimide monomer units (hereinafter referred to as "post-imidization method").

[0022] The polymerization mode of the maleimide copolymer (A) may be, for example, solution polymerization or bulk polymerization. From the viewpoint that the copolymerization while performing the portionwise addition or the like can obtain the maleimide copolymer (A) having a more uniform copolymerization composition, solution polymerization is preferred. The solvent for the solution polymerization is preferably non-polymerizable from the viewpoint that by-products are unlikely to be produced and adverse effects are small. For example, ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, acetophenone, etc., ethers such as tetrahydrofuran and 1,4-dioxane, aromatic hydrocarbons such as benzene, toluene, xylene, chlorobenzene, etc., N,N-dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, etc., and methyl ethyl ketone and methyl isobutyl ketone are preferred from the viewpoint of ease of solvent removal during volatilization and recovery of the maleimide copolymer (A). The polymerization process may be any of a continuous polymerization method, a batch method (batch method), and a semi-batch method. The polymerization method is not particularly limited, but radical polymerization is preferred from the viewpoint that it is possible to produce the copolymer with good productivity by a simple process.

[0023] In the solution polymerization or bulk polymerization, a polymerization initiator and a chain transfer agent can be used, and the polymerization temperature is preferably in the range of 80 to 150°C. The polymerization initiator is, for example, an azo compound such as azobisisobutyronitrile, azobiscyclohexanecarbonitrile, azobismethylproponitrile, or azobismethylbutyronitrile, or a peroxide such as benzoyl peroxide, t-butylperoxybenzoate, 1,1-di(t-butylperoxy)cyclohexane, t-butylperoxyisopropylmonocarbonate, t-butylperoxy-2-ethylhexanoate, di-t-butylperoxide, dicumylperoxide, or ethyl-3,3-di-(t-butylperoxy)butyrate, and one or more of these may be used in combination. From the viewpoint of the polymerization reaction rate and polymerization rate control, it is preferable to use an azo compound or an organic peroxide with a 10-hour half-life of 70 to 120°C. The amount of the polymerization initiator used is not particularly limited, but is preferably 0.1 to 1.5% by mass, more preferably 0.1 to 1.0% by mass, based on 100% by mass of the total monomer units. If the amount of the polymerization initiator used is 0.1% by mass or more, a sufficient polymerization rate can be obtained, which is preferable. If the amount of the polymerization initiator used is 1.5% by mass or less, the polymerization rate can be suppressed, making it easy to control the reaction and to easily obtain the target molecular weight. Examples of the chain transfer agent include n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, α-methylstyrene dimer, ethyl thioglycolate, limonene, and terpinolene. The amount of the chain transfer agent used is not particularly limited as long as it is within a range in which the target molecular weight can be obtained, but is preferably 0.1 to 0.8% by mass, more preferably 0.15 to 0.5% by mass, based on 100% by mass of the total monomer units. If the amount of the chain transfer agent used is 0.1% by mass to 0.8% by mass, the target molecular weight can be easily obtained.

[0024] The introduction of maleimide monomer units into the maleimide copolymer (A) can be achieved by copolymerizing maleimide monomers or by post-imidization. The post-imidization method is preferred because it reduces the amount of maleimide monomers remaining in the maleimide copolymer (A). The post-imidization method is a method in which a monomer mixture consisting of an aromatic vinyl monomer, an unsaturated dicarboxylic anhydride monomer, and other copolymerizable monomers is copolymerized, and then a part of the unsaturated dicarboxylic anhydride monomer units is imidized by reacting with ammonia or a primary amine to convert them into maleimide monomer units. Examples of primary amines include alkylamines such as methylamine, ethylamine, n-propylamine, iso-propylamine, n-butylamine, n-pentylamine, n-hexylamine, n-octylamine, cyclohexylamine, and decylamine, as well as aromatic amines such as alkylamines substituted with chlorine or bromine, aniline, toluidine, and naphthylamine, among which aniline is preferred. These primary amines may be used alone or in combination of two or more. In the post-imidization, a catalyst may be used to improve the dehydration ring-closing reaction in the reaction between the primary amine and the unsaturated dicarboxylic anhydride monomer unit. The catalyst is, for example, a tertiary amine such as trimethylamine, triethylamine, tripropylamine, tributylamine, N,N-dimethylaniline, or N,N-diethylaniline. The post-imidization temperature is preferably 100 to 250°C, more preferably 120 to 200°C. If the temperature of the imidization reaction is 100°C or higher, the reaction rate is improved, which is preferable from the viewpoint of productivity. If the temperature of the imidization reaction is 250°C or lower, it is preferable because the decrease in physical properties due to thermal deterioration of the maleimide copolymer (A) can be suppressed.

[0025] A known method can be used to remove volatile components such as the solvent used in the solution polymerization and unreacted monomers from the solution after the completion of solution polymerization of the maleimide copolymer (A) or the solution after the completion of post-imidization (devolatilization method). For example, a vacuum devolatilization tank equipped with a heater or a devolatilization extruder equipped with a vent can be used. The devolatilized molten maleimide copolymer (A) is transferred to a granulation process, extruded into strands through a multi-hole die, and processed into pellets by a cold cut method, an air hot cut method, or an underwater hot cut method.

[0026] The content of the maleimide copolymer (A) in the heat-resistant resin composition is preferably 5 to 40% by mass, more preferably 7 to 35% by mass, and further preferably 10 to 30% by mass. Specifically, for example, it is 5, 10, 15, 20, 25, 30, 35, 36, 37, 38, 39, or 40% by mass, and may be within a range between any two of the numerical values ​​exemplified here. If the content of the maleimide copolymer (A) is too small, the heat resistance of the heat-resistant resin composition may not be sufficiently improved. If it is too large, the flowability may decrease, and the moldability may deteriorate.

[0027] Resin (B) is selected from ABS resin, ASA resin, AES resin, and SAN resin, and may be one type or two or more types. When two or more types are used, it is preferable to use, for example, ABS resin and SAN resin in combination, ASA resin and SAN resin in combination, or AES resin and SAN resin in combination.

[0028] ABS resin, ASA resin, and AES resin are graft copolymers obtained by graft copolymerizing at least a styrene-based monomer and an acrylonitrile-based monomer onto a rubber-like polymer. For example, when a butadiene-based rubber such as polybutadiene or a styrene-butadiene copolymer is used as the rubber-like polymer, the resin is an ABS resin. When an acrylic rubber such as butyl acrylate or ethyl acrylate is used as the rubber-like polymer, the resin is an ASA resin. When an ethylene-based rubber such as an ethylene-α-olefin copolymer is used as the rubber-like polymer, the resin is an AES resin. Two or more of these rubber-like polymers may be used in combination during graft copolymerization.

[0029] A known method can be used to produce a graft copolymer such as an ABS resin. For example, a production method using emulsion polymerization or continuous bulk polymerization can be used. The method using emulsion polymerization is preferred because it is easy to adjust the content of the rubber-like polymer in the final ABS resin composition.

[0030] The method for producing a graft copolymer by emulsion polymerization includes a method in which a styrene monomer and an acrylonitrile monomer are emulsion-graft-copolymerized to a latex of a rubber-like polymer (hereinafter referred to as the "emulsion graft polymerization method"). A latex of a graft copolymer can be obtained by the emulsion graft polymerization method.

[0031] In the emulsion graft polymerization method, water, an emulsifier, a polymerization initiator, and a chain transfer agent are used, and the polymerization temperature is preferably in the range of 30 to 90°C. Examples of the emulsifier include an anionic surfactant, a nonionic surfactant, and an amphoteric surfactant. Examples of the polymerization initiator include organic peroxides such as cumene hydroperoxide, diisopropyl ene peroxide, t-butyl peroxyacetate, t-hexyl peroxybenzoate, and t-butyl peroxybenzoate, persulfates such as potassium persulfate and ammonium persulfate, azo compounds such as azobisbutyronitrile, reducing agents such as iron ions, secondary reducing agents such as sodium formaldehyde sulfoxylate, and chelating agents such as disodium ethylenediamine tetraacetate. Examples of the chain transfer agent include n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, α-methylstyrene dimer, ethyl thioglycolate, limonene, and terpinolene.

[0032] The latex of the graft copolymer can be coagulated by a known method, and the graft copolymer can be recovered. For example, a coagulant is added to the latex of the graft copolymer to coagulate it, and the coagulated latex is washed and dehydrated in a dehydrator, and then a drying process is performed to obtain a powdery graft copolymer.

[0033] The content of the residual monomer in the powdered graft copolymer obtained by the emulsion graft polymerization method is preferably less than 15,000 μg / g, more preferably less than 8,000 μg / g. The content of the residual monomer can be adjusted by the polymerization conditions, and is a value determined by gas chromatography.

[0034] The content of the rubber-like polymer in the graft copolymer obtained by emulsion graft polymerization is preferably 40 to 70% by mass, more preferably 45 to 65% by mass, from the viewpoint of impact resistance. The content of the rubber-like polymer can be adjusted, for example, by changing the ratio of the styrene-based monomer and the acrylonitrile-based monomer to the rubber-like polymer during emulsion graft polymerization.

[0035] From the viewpoints of impact resistance and chemical resistance, the constituent units excluding the rubber-like polymer of the graft copolymer obtained by emulsion graft polymerization preferably contain 65 to 85 mass % of styrene-based monomer units and 15 to 35 mass % of acrylonitrile-based monomer units.

[0036] The gel fraction of the graft copolymer is preferably in the form of particles. The gel fraction is a particle of a rubber-like polymer in which a styrene-based monomer and an acrylonitrile-based monomer are graft-copolymerized, and is a component that is insoluble in organic solvents such as methyl ethyl ketone and toluene and is separated by centrifugation. An occlusion structure in which a styrene-acrylonitrile copolymer is encapsulated in the form of particles may be formed inside the rubber-like polymer particles. When the graft copolymer and the styrene-acrylonitrile copolymer are melt-blended, the gel fraction exists in the form of particles as a dispersed phase in the continuous phase of the styrene-acrylonitrile copolymer. The gel fraction is a value calculated by dissolving a mass W of the graft copolymer in methyl ethylene ketone, centrifuging the mixture at 20,000 rpm using a centrifuge to settle the insoluble fraction, removing the supernatant by decantation to obtain the insoluble fraction, and calculating the mass S of the dried insoluble fraction after vacuum drying using the formula: gel fraction (mass%) = (S / W) x 100. Similarly, an ABS resin composition obtained by melt-blending a graft copolymer and a styrene-acrylonitrile copolymer can be dissolved in methyl ethyl ketone and centrifuged to calculate the gel content.

[0037] The volume average particle size of the gel portion of the graft copolymer is preferably in the range of 0.10 to 1.0 μm, more preferably 0.15 to 0.50 μm, from the viewpoint of impact resistance and the appearance of the molded product. The volume average particle size is a value calculated from an image analysis of particles dispersed in a continuous phase by cutting ultra-thin slices from pellets of an ABS resin composition obtained by melt-blending a graft copolymer with a styrene-acrylonitrile copolymer, observing the slices with a transmission electron microscope (TEM). The volume average particle size can be adjusted, for example, by the particle size of the latex of the rubber-like polymer used in emulsion graft polymerization. The particle size of the latex of the rubber-like polymer can be adjusted by the method of adding an emulsifier or the amount of water used during emulsion polymerization, but in order to achieve a preferred range, the polymerization time is long and the productivity is low, so there is a method in which a rubber-like polymer with a particle size of about 0.1 μm is polymerized in a short time, and the rubber particles are enlarged using a chemical coagulation method or a physical coagulation method.

[0038] From the viewpoint of impact resistance, the graft ratio of the graft copolymer is preferably 10 to 100% by mass, more preferably 20 to 70% by mass. The graft ratio is a value calculated from the gel content (G) and the content of the rubber-like polymer (RC) by the formula: graft ratio (mass%) = [(G-RC) / R] x 100. The graft ratio represents the amount of styrene-acrylonitrile copolymer bound to the rubber-like polymer particles by the graft contained per unit mass of the rubber-like polymer and the amount of styrene-acrylonitrile copolymer contained in the particles. The graft ratio can be adjusted, for example, by the ratio of the monomer to the rubber-like polymer, the type and amount of the initiator, the amount of the chain transfer agent, the amount of the emulsifier, the polymerization temperature, the method of charging (lump / multi-stage / continuous), the rate of addition of the monomer, and the like, during emulsion graft polymerization.

[0039] SAN resin is a copolymer having styrene-based monomer units and acrylonitrile-based monomer units, and an example is a styrene-acrylonitrile copolymer.

[0040] Other copolymerizable monomers for SAN resin include (meth)acrylic acid ester monomers such as methyl methacrylate, acrylic acid ester monomers such as butyl acrylate and ethyl acrylate, (meth)acrylic acid monomers such as methacrylic acid, acrylic acid monomers such as acrylic acid, and N-substituted maleimide monomers such as N-phenylmaleimide.

[0041] The constituent units of the SAN resin are preferably 60 to 90% by mass of styrene monomer units and 10 to 40% by mass of vinyl cyanide monomer units, and more preferably 65 to 80% by mass of styrene monomer units and 20 to 35% by mass of vinyl cyanide monomer units. If the constituent units are within the above ranges, the resulting heat-resistant resin composition has an excellent balance between impact strength and fluidity. The values ​​of the styrene monomer units and vinyl cyanide monomer units are values ​​measured by 13C-NMR.

[0042] A known method can be used to produce SAN resin. For example, it can be produced by bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. As the operation method of the reaction apparatus, any of a continuous type, a batch type (batch type), and a semi-batch type can be applied. From the viewpoints of quality and productivity, bulk polymerization or solution polymerization is preferred, and continuous type is preferred. Examples of the solvent for bulk polymerization or solution polymerization include alkylbenzenes such as benzene, toluene, ethylbenzene, and xylene, ketones such as acetone and methyl ethyl ketone, and aliphatic hydrocarbons such as hexane and cyclohexane.

[0043] In bulk polymerization or solution polymerization of SAN resin, a polymerization initiator and a chain transfer agent can be used, and the polymerization temperature is preferably in the range of 120 to 170° C. Examples of the polymerization initiator include peroxyketals such as 1,1-di(t-butylperoxy)cyclohexane, 2,2-di(t-butylperoxy)butane, 2,2-di(4,4-di-t-butylperoxycyclohexyl)propane, and 1,1-di(t-amylperoxy)cyclohexane; hydroperoxides such as cumene hydroperoxide and t-butyl hydroperoxide; alkyl peroxides such as t-butyl peroxyacetate and t-amyl peroxyisononanoate; dialkyl peroxides such as t-butylcumyl peroxide, di-t-butyl peroxide, dicumyl peroxide, and di-t-hexyl peroxide; peroxyesters such as t-butylperoxyacetate, t-butylperoxybenzoate, and t-butylperoxyisopropyl monocarbonate; peroxycarbonates such as t-butylperoxyisopropyl carbonate and polyethertetrakis(t-butylperoxycarbonate); N,N'-azobis(cyclohexane-1-carbonitrile), N,N'-azobis(2-methylbutyronitrile), N,N'-azobis(2,4-dimethylvaleronitrile), and N,N'-azobis[2-(hydroxymethyl)propionitrile]; and these may be used alone or in combination of two or more. Examples of chain transfer agents include n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, α-methylstyrene dimer, ethyl thioglycolate, limonene, and terpinolene.

[0044] A known method can be used to remove volatile components such as unreacted monomers and the solvent used in the solution polymerization from the solution after the polymerization of SAN resin is completed. For example, a vacuum devolatilization tank equipped with a preheater or a devolatilization extruder equipped with a vent can be used. The devolatilized SAN resin in a molten state is transferred to a granulation process, extruded into strands through a multi-hole die, and processed into pellets by a cold cut method, an air hot cut method, or an underwater hot cut method.

[0045] The total content of the monomer and the solvent remaining in the SAN resin is preferably less than 2000 μg / g, and more preferably less than 1500 μg / g. The content of the remaining monomer and the solvent can be adjusted by the devolatilization conditions, and is a value quantified by gas chromatography.

[0046] From the viewpoint of impact resistance and moldability of the resulting heat-resistant resin composition, the weight average molecular weight of the SAN resin is preferably 50,000 to 250,000, and more preferably 70,000 to 200,000.Specific examples of the weight average molecular weight include 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, 150,000, 160,000, 170,000, 180,000, 190,000, and 200,000, and may be within a range between any two of the numerical values ​​exemplified here. The weight average molecular weight of the SAN resin is a value measured in THF solvent by gel permeation chromatography (GPC) in terms of polystyrene, and is a value measured in the same manner as for the maleimide copolymer (A). The weight average molecular weight can be adjusted by the type and amount of chain transfer agent, solvent concentration, polymerization temperature, and type and amount of polymerization initiator during polymerization.

[0047] For example, two types of resin (B) may be used: a powdered ABS resin obtained by emulsion polymerization and a pelleted SAN resin obtained by continuous bulk polymerization. Another method is to use a pelleted ABS resin obtained by melt-blending a powdered ABS resin obtained by emulsion polymerization and a pelleted SAN resin obtained by continuous bulk polymerization in an extruder or the like.

[0048] A known method can be used for melt-kneading and devolatilizing extrusion of the maleimide copolymer (A) and at least one resin (B) selected from ABS resin, ASA resin, AES resin, and SAN resin using an extruder. Known devices can be used as the extruder, and examples of such devices include twin-screw extruders, single-screw extruders, multi-screw extruders, and continuous kneaders with twin rotors. Intermeshing co-rotating twin-screw extruders are generally widely used and can be used preferably. A combination of a plurality of these extruders can also be used.

[0049] The extruder is composed of a kneading section for melt-kneading the maleimide copolymer (A) and the resin (B) and at least one devolatilizing section. The maleimide copolymer (A) and the resin (B) fed to the extruder are first melted in the kneading section and kneaded to a uniform composition. The kneading section is composed of a combination of known mixing elements such as kneading disks. From the viewpoint of kneading performance, it is preferable to use an element having the effect of pushing back the molten resin to the upstream side downstream of the kneading section and fill the kneading section. Examples of the element include a reverse lead full flight, a reverse offset kneading, and a seal ring.

[0050] The heat-resistant resin composition melt-kneaded in the kneading section is transported in a molten state to a devolatilizing section, where volatile components are devolatilized by a vacuum vent. The devolatilized molten heat-resistant resin composition is extruded in a strand shape from a multi-hole die, and the pellet-shaped heat-resistant resin composition is obtained by a cold cut method, an air hot cut method, or an underwater hot cut method.

[0051] As a method of devolatilization extrusion, a water injection devolatilization method in which water is added before the devolatilization section is preferred because it has excellent devolatilization efficiency. For example, a method can be mentioned in which, after melt-kneading the maleimide copolymer (A) and the resin (B) in the kneading section, a further kneading section is provided, water is uniformly kneaded and dispersed in the molten resin, and volatile components are devolatilized together with water in the upstream devolatilization section. It is also preferable that the kneading section in which water is added and kneaded is filled up. The amount of water added is preferably 0.05 to 2.0 parts by mass per 100 parts by mass of the total amount of the maleimide copolymer (A) and the resin (B). The water content of the maleimide copolymer (A) and the resin (B) also effectively improves the devolatilization efficiency, but if it is too much, it may cause problems in the operation of the extruder.

[0052] The cylinder temperature of the kneading section and the devolatilizing section of the extruder is preferably set to 240°C or higher, more preferably 260°C or higher, and even more preferably 280°C or higher. By setting the cylinder temperature high, the devolatilizing efficiency is increased. In particular, since the heat-resistant resin composition using the maleimide-based copolymer has excellent thermal stability, the volatile components can be reduced by setting the cylinder temperature high. On the other hand, since the heat-resistant resin composition using the α-methylstyrene-based copolymer has poor thermal stability, if the cylinder temperature is set high, a large amount of α-methylstyrene generated by thermal decomposition is contained. The pressure of the devolatilizing section is preferably set to 10 mmHg or less when water is not added, and 40 mmHg or less when water is added.

[0053] The content of the volatile components calculated from the blend of the maleimide copolymer (A) and the resin (B) fed to the extruder is preferably less than 3,000 μg / g. If the content of the volatile components before extrusion is too high, it may be difficult to reduce the content of the volatile components in the heat-resistant resin composition.

[0054] The content of the rubber-like polymer in the heat-resistant resin composition is preferably 10 to 20% by mass. If the content is too low, the impact resistance may decrease, and if the content is too high, the rigidity and the deflection temperature under load may decrease.

[0055] The content of acrylonitrile monomer units in the continuous phase obtained by separating the gel content from the heat-resistant resin composition is preferably 15 to 35% by mass, more preferably 20 to 30% by mass. If the content is too low, the impact resistance may decrease, and if the content is too high, the fluidity may decrease. The heat-resistant resin composition is dissolved in methyl ethyl ketone, and the gel content is separated as an insoluble matter by centrifugation, and the supernatant obtained by decantation is precipitated with methanol to obtain the components of the continuous phase.

[0056] The heat-resistant resin composition has a ratio G' / G'' of storage modulus (G') to loss modulus (G'') at 240° C. and an angular velocity of 0.63 rad / s, as measured in accordance with JIS K 7244-10, of 0.30 or more and 1.00 or less. Here, if the ratio G' / G'' of the storage modulus (G') to the loss modulus (G'') is less than 0.30, the heat-resistant resin composition will have poor stringiness. If it exceeds 1.00, the heat-resistant resin composition will have poor chemical resistance. The ratio G' / G'' is preferably 0.40 or more and 1.00 or less, more preferably 0.60 or more and 1.00 or less. Specifically, the ratio is, for example, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, or 1.00, and may be within a range between any two of the numerical values ​​exemplified here.

[0057] The ratio G' / G'' can be adjusted in the following ways: For example, the ratio G' / G'' can be increased by adding a rubber component as an additive. From the viewpoint of the effect of increasing the ratio G' / G'', a non-crosslinked rubber component is preferable as the rubber component. More specifically, polyacrylic polymers, polybutadiene polymers, and the like are preferable. One type of such additive may be used, or two or more types may be used. The G' / G'' ratio can also be increased by increasing the molecular weight of the AS resin or maleimide copolymer used or by increasing the amount of ABS resin used. These methods may be used in combination.

[0058] The melt mass flow rate (220°C, 10 kg) of the heat-resistant resin composition measured by the method described in JIS K 7210 is preferably 5 to 30 g / 10 min, more preferably 15 to 20 g / 10 min. Specifically, for example, it is 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 25, or 30, and may be within a range between any two of the numerical values ​​exemplified here. If the melt mass flow rate is too low, chemical resistance and moldability may decrease, and if it is too high, stringiness may deteriorate.

[0059] To increase the melt mass flow rate of a heat-resistant resin composition, there are a method of adding a flowability modifier such as silicone oil, and a method of lowering the molecular weight of the AS resin or maleimide copolymer to be blended. To decrease the melt mass flow rate, there are a method of increasing the amount of ABS resin to be blended, and a method of increasing the molecular weight of the AS resin or maleimide copolymer to be blended. Two or more of these methods may be used in combination.

[0060] The Vicat softening temperature of the heat-resistant resin composition is a value measured by the 50 method (load 50N, temperature rise rate 50°C / hour) based on JIS K7206, and is preferably 105°C to 130°C, more preferably 110°C to 120°C. Specifically, for example, it is 105, 110, 111, 112, 113, 114, 115, 116, 117, 118, 119, 120, 121, 122, 123, 124, 125, or 130, and may be within a range between any two of the values ​​exemplified here. If the Vicat softening temperature is less than 105°C, the heat resistance of the heat-resistant resin composition is poor. Also, if it exceeds 130°C, the moldability and chemical resistance of the heat-resistant resin composition are poor.

[0061] The Vicat softening temperature of the heat-resistant resin composition can be adjusted by adjusting the type and amount of the maleimide-based copolymer in the heat-resistant resin composition. For example, in order to increase this value, there are methods of increasing the blending amount of the maleimide-based copolymer and methods of increasing the maleimide-based monomer units in the maleimide-based copolymer.

[0062] The heat-resistant resin composition may contain other resin components, impact resistance modifiers, flowability modifiers, hardness modifiers, antioxidants, inorganic fillers, matting agents, flame retardants, flame retardant assistants, drip prevention agents, sliding properties imparting agents, heat dissipation materials, electromagnetic wave absorbing materials, plasticizers, lubricants, release agents, ultraviolet absorbing agents, light stabilizers, antibacterial agents, antifungal agents, antistatic agents, carbon black, titanium oxide, pigments, dyes, and the like, within the scope of not impairing the effects of the present invention.

[0063] Furthermore, the heat-resistant composition may contain a non-crosslinkable rubber component such as a poly(meth)acrylic polymer, a polybutadiene polymer, or a polyolefin polymer in order to adjust the value of the ratio G' / G''.

[0064] Examples of non-crosslinkable rubber components include poly(meth)acrylic polymers such as polybutyl acrylate, polyethyl (meth)acrylate, polypropyl (meth)acrylate, polyoctyl (meth)acrylate, and poly(2-ethyl)hexyl (meth)acrylate, polybutadiene polymers such as polybutadiene, and polyolefin polymers such as polyethylene and polypropylene, and preferably poly(meth)acrylic polymers and polybutadiene polymers. These may be used alone or in combination of two or more kinds. In addition, these may be homopolymers or copolymers with monomers copolymerizable therewith.

[0065] The heat-resistant resin composition can be molded by a known method. Examples of the molding method include injection molding, sheet extrusion molding, vacuum molding, blow molding, foam molding, and irregular extrusion molding. During molding, the heat-resistant resin composition is usually heated to 200 to 280°C and then processed, but preferably 210 to 270°C. Molded products can be used for automobiles, home appliances, OA equipment, housing construction materials, daily necessities, and the like. Since the heat-resistant resin composition of the present invention has excellent thermal stability, the content of volatile components does not change significantly even when molded at high temperatures. On the other hand, in the heat-resistant resin composition using an α-methylstyrene copolymer, α-methylstyrene is generated by thermal decomposition of the α-methylstyrene copolymer depending on the resin temperature and residence time in the molding machine, and is contained in a large amount in the molded product. EXAMPLES

[0066] The following detailed description will be given using examples, but the present invention is not limited to the following examples.

[0067] <Production Example of Maleimide Copolymer (A-1)> In an autoclave with a volume of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 5 parts by mass of maleic anhydride, 0.1 parts by mass of t-butylperoxy-2-ethylhexanoate, 0.25 parts by mass of α-methylstyrene dimer, and 12 parts by mass of methyl ethyl ketone were charged, and the gas phase was replaced with nitrogen gas, and then the temperature was raised to 92°C over 40 minutes while stirring. After the temperature was raised to 92°C, a solution in which 28 parts by mass of styrene, 30 parts by mass of maleic anhydride, and 0.22 parts by mass of t-butylperoxy-2-ethylhexanoate were dissolved in 75 parts by mass of methyl ethyl ketone was continuously added over 7 hours. After the addition of maleic anhydride was completed, 17 parts by mass of styrene was continuously added over 2 hours. After the addition of styrene, the temperature was raised to 120°C, and the reaction was carried out for 1 hour to complete the polymerization. Thereafter, 21.2 parts by mass of aniline and 0.3 parts by mass of triethylamine were added to the polymerization solution and reacted at 140°C for 7 hours. After the reaction was completed, the imidization reaction solution was fed into a vent-type screw extruder, and volatile components were removed to obtain a pellet-shaped maleimide copolymer A-1. The constituent units were 51% by mass of styrene units, 48% by mass of N-phenylmaleimide units, and 1% by mass of maleic anhydride units. The midpoint glass transition temperature (Tmg) measured by DSC was 186°C. The weight average molecular weight was 90,000.

[0068] <Production Example of Maleimide Copolymer (A-2)> In an autoclave with a volume of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 5 parts by mass of maleic anhydride, 0.1 parts by mass of t-butylperoxy-2-ethylhexanoate, 0.13 parts by mass of α-methylstyrene dimer, and 12 parts by mass of methyl ethyl ketone were charged, and the gas phase was replaced with nitrogen gas, and then the temperature was raised to 92°C over 40 minutes while stirring. After the temperature was raised to 92°C, a solution in which 28 parts by mass of styrene, 35 parts by mass of maleic anhydride, and 0.22 parts by mass of t-butylperoxy-2-ethylhexanoate were dissolved in 75 parts by mass of methyl ethyl ketone was continuously added over 7 hours. After the addition of maleic anhydride was completed, 12 parts by mass of styrene was continuously added over 2 hours. After the addition of styrene, the temperature was raised to 120°C, and the reaction was carried out for 1 hour to complete the polymerization. Thereafter, 23.1 parts by mass of aniline and 0.3 parts by mass of triethylamine were added to the polymerization solution and reacted at 140°C for 7 hours. After the reaction was completed, the imidization reaction solution was fed into a vent-type screw extruder, and volatile components were removed to obtain a pellet-shaped maleimide copolymer A-2. The constituent units were 47% by mass of styrene units, 52% by mass of N-phenylmaleimide units, and 1% by mass of maleic anhydride units. The midpoint glass transition temperature (Tmg) measured by DSC was 195°C. The weight average molecular weight was 130,000.

[0069] <Production Example of Maleimide Copolymer (A-3)> Into an autoclave with a volume of about 120 liters equipped with a stirrer, 20 parts by mass of styrene, 10 parts by mass of acrylonitrile, 5 parts by mass of maleic anhydride, 0.1 part by mass of t-butyl peroxy-2-ethylhexanoate, 0.10 part by mass of α-methylstyrene dimer, and 12 parts by mass of methyl ethyl ketone were charged. After replacing the gas phase part with nitrogen gas, the temperature was raised to 92°C over 40 minutes while stirring. While maintaining 92°C after the temperature rise, a solution prepared by dissolving 28 parts by mass of styrene, 34 parts by mass of maleic anhydride, and 0.22 part by mass of t-butyl peroxy-2-ethylhexanoate in 75 parts by mass of methyl ethyl ketone was continuously added over 7 hours. Further, after the addition of maleic anhydride was completed, 13 parts by mass of styrene was continuously added over 2 hours. After the addition of styrene, the temperature was raised to 120°C and the reaction was carried out for 1 hour to complete the polymerization. Thereafter, 20.7 parts by mass of aniline and 0.3 part by mass of triethylamine were added to the polymerization solution and reacted at 140°C for 7 hours. The imidized reaction solution after the reaction was charged into a vent type screw extruder to remove volatile components, and a pelletized maleimide copolymer A-3 was obtained. The constituent units were 48% by mass of styrene units, 46% by mass of N-phenylmaleimide units, and 6% by mass of maleic anhydride units. The midpoint glass transition temperature (Tmg) measured by DSC was 195°C. Also, the weight average molecular weight was 140,000.

[0070] <Production Example of ABS Resin (ABS-1)> The ABS resin was produced by the emulsion graft polymerization method. 97 parts by mass of polybutadiene latex (solid content concentration: 50% by mass, average particle diameter: 0.3 μm), 12 parts by mass of styrene-butadiene latex with a styrene content of 24% by mass (solid content concentration: 70% by mass, average particle diameter: 0.5 μm), 1 part by mass of sodium stearate, 0.2 part by mass of sodium formaldehyde sulfoxylate, 0.01 part by mass of tetrasodium ethylenediaminetetraacetate, 0.005 part by mass of ferrous sulfate, and 200 parts of pure water were charged into a reaction kettle equipped with a stirrer, and the temperature was heated to 50°C. 43 parts by mass of a monomer mixture of 75% by mass of styrene and 25% by mass of acrylonitrile, 0.2 part by mass of t-dodecyl mercaptan, and 0.06 part by mass of t-butyl peroxyacetate were continuously added in portions over 5 hours. After the completion of the addition in portions, 0.04 part by mass of diisopropylbenzene peroxide was added, and the polymerization was completed at 70°C over 2 more hours to obtain a latex of the ABS resin. After adding 0.3 part of Irganox 1076 (manufactured by BASF Japan Ltd.) to the obtained latex, coagulation was carried out using magnesium sulfate and sulfuric acid so that the pH of the slurry during coagulation was 6.8. After washing, dehydration, and drying, a powdery ABS resin was obtained. From the blending ratio of the raw materials, the rubbery polymer content was 57% by mass. The structural units excluding the rubbery polymer were measured by NMR, and the styrene unit was 75% by mass and the acrylonitrile unit was 25% by mass. From the observation with a transmission electron microscope, the ABS resin was dispersed in a particulate form, and the volume average particle diameter was 0.4 μm. The content of volatile components in the ABS resin was 6,000 μg / g for styrene and less than the detection limit (30 μg / g) for acrylonitrile.

[0071] <Production Example of SAN Resin (SAN-1)> The SAN resin was produced by continuous bulk polymerization. One completely mixed tank-type stirred tank was used as the reactor, and polymerization was carried out with a capacity of 20 L. A raw material solution consisting of 60% by mass of styrene, 22% by mass of acrylonitrile, and 18% by mass of ethylbenzene was prepared and continuously supplied to the reactor at a flow rate of 6.5 L / h. Also, t-butyl peroxyisopropyl monocarbonate was continuously added to the supply line of the raw material solution at a concentration of 160 ppm as a polymerization initiator, and n-dodecyl mercaptan was continuously added at a concentration of 400 ppm as a chain transfer agent. The reaction temperature of the reactor was adjusted to 145°C. The polymer solution continuously withdrawn from the reactor was supplied to a vacuum devolatilization tank equipped with a preheater to separate unreacted styrene, acrylonitrile, and ethylbenzene. The temperature of the preheater was adjusted so that the polymer temperature in the devolatilization tank was 225°C, and the pressure in the devolatilization tank was 0.4 kPa. The polymer was extracted from the vacuum devolatilization tank by a gear pump, extruded in a strand shape, cooled with cooling water, and cut to obtain pellet-shaped SAN resin. The constituent units were 74% by mass of styrene units and 26% by mass of acrylonitrile units. Also, the weight average molecular weight was 100,000.

[0072] <Production Example of SAN Resin (SAN-2)> The SAN resin was produced by continuous bulk polymerization. One completely mixed tank-type stirred tank was used as the reactor, and polymerization was carried out with a capacity of 20 L. A raw material solution composed of 57% by mass of styrene, 25% by mass of acrylonitrile, and 18% by mass of ethylbenzene was prepared and continuously supplied to the reactor at a flow rate of 6.5 L / h. Also, t-butyl peroxyisopropyl monocarbonate was continuously added to the supply line of the raw material solution at a concentration of 160 ppm as a polymerization initiator, and n-dodecyl mercaptan was continuously added at a concentration of 400 ppm as a chain transfer agent. The reaction temperature of the reactor was adjusted to 145°C. The polymer solution continuously withdrawn from the reactor was supplied to a vacuum devolatilization tank equipped with a preheater to separate unreacted styrene, acrylonitrile, and ethylbenzene. The temperature of the preheater was adjusted so that the polymer temperature in the devolatilization tank was 225°C, and the pressure in the devolatilization tank was 0.4 kPa. The polymer was extracted from the vacuum devolatilization tank by a gear pump, extruded in a strand shape, cooled with cooling water, and cut to obtain pellet-shaped SAN resin. The constituent units were 70% by mass of styrene units and 30% by mass of acrylonitrile units. Also, the weight average molecular weight was 120,000.

[0073] <Production Example of SAN Resin (SAN-3)> SAN resin was produced by continuous bulk polymerization. One complete mixing type stirring tank was used as the reactor, and polymerization was carried out with a volume of 20 L. A raw material solution of 60 mass% styrene, 22 mass% acrylonitrile, and 18 mass% ethylbenzene was prepared and continuously supplied to the reactor at a flow rate of 6.5 L / h. In addition, t-butylperoxyisopropyl monocarbonate was continuously added to the raw material solution supply line as a polymerization initiator to a concentration of 160 ppm. The reaction temperature of the reactor was adjusted to 145 ° C. The polymer solution continuously taken out from the reactor was supplied to a vacuum devolatilizer tank equipped with a preheater, and unreacted styrene, acrylonitrile, and ethylbenzene were separated. The temperature of the preheater was adjusted so that the polymer temperature in the devolatilizer tank was 225 ° C., and the pressure in the devolatilizer tank was 0.4 kPa. The polymer was extracted from the vacuum devolatilizer tank using a gear pump, extruded in the form of a strand, cooled with cooling water, and then cut to obtain a pellet-shaped SAN resin. The structural units were 70% by mass of styrene units and 30% by mass of acrylonitrile units. The weight average molecular weight was 145,000.

[0074] <Additives-1> HP4051 manufactured by Dow Mitsui Polychemicals Co., Ltd. was used as additive-1.

[0075] <Additives-2> Additive 2 used was L-1000 manufactured by Mitsubishi Chemical Corporation.

[0076] <Additives-3> As additive 3, SH-200 10CS manufactured by Shigewa Sangyo Co., Ltd. was used.

[0077] <Additives-4> As additive 4, PEG-20000 manufactured by Sanyo Chemical Industries, Ltd. was used.

[0078] <Examples and Comparative Examples> A maleimide copolymer, an ABS resin, and a SAN resin were melt-kneaded and extruded with a devolatilization using an extruder in the composition shown in Table 1 to obtain a heat-resistant resin composition. The extruder used was a twin-screw extruder (TEM-35B, manufactured by Toshiba Machine Co., Ltd.). The extruder was configured such that a kneading section for melt-kneading each resin was first provided, a kneading section for adding and kneading water was then provided, and a devolatilization section was then provided. The cylinder temperatures of the kneading section and the devolatilization section were set to the temperatures shown in Table 1, and extrusion was performed at a screw rotation speed of 250 rpm and a feed rate of 30 kg / hr. Water was added so as to be 0.5% by mass relative to the feed rate, and the pressure in the devolatilization section was 10 mmHg. The obtained heat-resistant resin composition was evaluated as follows. The evaluation results are shown in Tables 1 and 2.

[0079] (G′ / G′′) G' / G'' was measured using a viscoelasticity measuring device DHR manufactured by TA Instruments. Measurements were performed using 25 mm parallel plates with a gap of 0.75 mm, strain of 5%, and a measurement temperature of 240°C. The values ​​of G' / G'' at an angular velocity of 0.63 rad / s are shown in Tables 1 and 2.

[0080] (Vicat softening temperature) The Vicat softening point was measured using a test piece of 10 mm x 10 mm and 4 mm thick, according to the JIS K7206 50 method (load 50N, heating rate 50℃ / hour). The measuring machine used was a HDT&VSPT tester manufactured by Toyo Seiki Seisakusho Co., Ltd.

[0081] (Melt Mass Flow Rate) The melt mass flow rate was measured at 220° C. under a load of 10 kg in accordance with JIS K7210.

[0082] (Charpy impact strength) The Charpy impact strength was measured based on JIS K7111-1 using a notched test piece and edgewise impact direction. The measuring machine used was a digital impact tester manufactured by Toyo Seiki Seisakusho Co., Ltd.

[0083] (Stringiness) Based on JIS K-7171, stringiness was evaluated using a test piece measuring 80 mm x 10 mm x 4 mm, which was pressed against a hot plate at 240°C with a load of 1 kg for 10 seconds and then pulled up at a speed of 10 cm / sec. The stringiness was evaluated on a five-point scale as follows: A: The thread breaks when the thread is pulled 1.0 cm or less, B: The thread breaks when the thread is pulled 1.0 cm to 4.0 cm, C: The thread breaks when the thread is pulled 4.0 cm to 7.0 cm, D: The thread breaks when the thread is pulled 7.0 cm to 10.0 cm, E: The thread is pulled 10 cm or more.

[0084] (Chemical resistance) The cracks were observed after 48 hours at 23℃ using the 1 / 4 ellipse method with a test specimen shape of 316×20×2mm, long radius of 250mm, and short radius of 150mm. In order to eliminate the influence of molding strain, the test specimens were produced by pressing pellets at 260℃ and cutting them out. Toluene was used as the chemical. The critical strain was calculated using the following formula. ε=b / 2a 2 {1-(a 2 -b 2 )X 2 / a 4} 1.5 ×t×100 Critical strain: ε, major axis: a, minor axis: b, test thickness: t, crack initiation point: X The chemical resistance was evaluated based on the critical strain according to the following criteria. A: 0.8 or more, B: 0.6~0.7, C: 0.3~0.5, D: 0.2 or less

[0085] [Table 1]

[0086] [Table 2]

[0087] From the results of Tables 1 and 2, it was found that resins with a G' / G'' of 0.30 to 1.00 improved stringiness, resulting in a heat-resistant resin composition with an excellent balance between heat resistance and appearance. Examples 1 to 11 had high chemical resistance, and Examples 5 and 9 to 11 in particular had particularly excellent chemical resistance. It was also revealed that when the MFR of the resin was set to 5 or more, a resin with even better chemical resistance could be obtained. Furthermore, when additives were used, it was possible to improve stringiness by increasing G' / G''.

[0088] Although much remains unclear about the mechanism by which stringiness is improved by controlling G' / G'', it is believed that an index related to the dynamic viscoelasticity of the resin composition in a molten state during hot plate fusion affects stringiness. The present invention has made it clear that, among the indexes related to dynamic viscoelasticity, controlling G' / G'' in particular within a specific range contributes greatly to improving stringiness. [Industrial Applicability]

[0089] By using the heat-resistant resin composition of the present invention, it is possible to mold without any defective appearance even when bonding is performed by hot plate fusion, which is an inexpensive bonding technique. Furthermore, even when a high-fluidity resin that improves production efficiency is used, it is possible to mold without any defective appearance by hot plate fusion. Furthermore, by setting the G' / G'' of the resin within the above range, it is possible to obtain a heat-resistant resin composition that is excellent in balance between fluidity, chemical resistance, heat resistance, and appearance, and it can be suitably used for automobiles, home appliances, office equipment, housing construction materials, daily necessities, etc.

Claims

1. A composition comprising a maleimide-based copolymer (A) and at least one resin (B) selected from ABS resin, ASA resin, AES resin, and SAN resin, The composition contains 0 to 2 parts by mass of a non-crosslinkable rubber component relative to 100 parts by mass of the total of the maleimide-based copolymer (A) and the resin (B), The composition contains 5 to 40% by mass of the maleimide-based copolymer (A) and 60 to 95% by mass of the resin (B), The maleimide copolymer (A) has a weight average molecular weight of 80,000 to 160,000; The resin (B) contains at least a SAN resin, and the weight average molecular weight of the SAN resin is 50,000 to 250,000; the resin (B) contains at least an ABS resin, and the content ratio (mass ratio) of the ABS resin to the resin other than the ABS resin in the resin (B) is 20:70 to 20:50; A heat-resistant resin composition having a ratio G' / G'' of storage modulus (G') to loss modulus (G'') at 240°C and an angular velocity of 0.63 rad / s, as measured in accordance with JIS K 7244-10, of 0.30 or more and 1.00 or less.

2. A composition comprising a maleimide-based copolymer (A) and at least one resin (B) selected from ABS resin, ASA resin, AES resin, and SAN resin, The composition contains 0 to 2 parts by mass of a non-crosslinkable rubber component relative to 100 parts by mass of the total of the maleimide-based copolymer (A) and the resin (B), The composition contains 5 to 40% by mass of the maleimide-based copolymer (A) and 60 to 95% by mass of the resin (B), The maleimide copolymer (A) has a weight average molecular weight of 80,000 to 160,000; The resin (B) contains at least a SAN resin, and the weight average molecular weight of the SAN resin is 50,000 to 250,000; the resin (B) contains at least an ABS resin, and the content ratio (mass ratio) of the ABS resin to the SAN resin in the resin (B) is 20:70 to 20:50; A heat-resistant resin composition having a ratio G' / G'' of storage modulus (G') to loss modulus (G'') at 240°C and an angular velocity of 0.63 rad / s, as measured in accordance with JIS K 7244-10, of 0.30 or more and 1.00 or less.

3. 3. The heat-resistant resin composition according to claim 1, wherein the maleimide-based copolymer (A) is composed of 40 to 60% by mass of aromatic vinyl monomer units and 60 to 40% by mass of maleimide-based monomer units.

4. The heat-resistant resin composition according to any one of claims 1 to 3, wherein the melt mass flow rate, measured by the method described in JIS K 7210 under conditions of 220 ° C. and 10 kg, is 5 to 30 g / 10 min.

5. The heat-resistant resin composition according to any one of claims 1 to 4, which has a Vicat softening temperature of 105°C to 130°C as measured by the method described in JIS K-7206.

6. An injection molded article using the heat-resistant resin composition according to any one of claims 1 to 5.

7. The injection molded article according to claim 6, which is used as an interior or exterior member of an automobile.

Citation Information

Patent Citations

  • Heat-resistant resin composition

    JP1982098536A

  • Thermoplastic resin composition

    JP1982125242A

  • Thermoplastic resin composition and molded article both excellent in heat-resistance and chemical resistance

    JP2004323772A

  • Heat-resistant resin composition and method for producing same

    WO2016186133A1

  • Component libraries for voice interaction services

    WO2018026554A1